EARTH WILL SURVIVE* : *but we may not - Coppens, Katie, 1979- (Boston, MA : Tumblehome, Inc., 2021)
"What is Earth's history, including the history of life? Where is Earth headed, and what can we do? A middle school science teacher addresses these questions with a friendly narrative voice and a focus both on how science is done and the diverse people who do it. Women like Mary Anning and Rachel Carson get equal attention to men like James Hutton and Georges Cuvier. Present problems of the Earth discussed include not only climate change but human-caused extinctions, plastic pollution, and invasive species. A final section suggests things kids can do to make a difference, from changing their behavior as consumers to recycling, energy use, and voting." Provided by publisher
Bibliography: pages 190.
Keywords: Human ecology -- Juvenile literature; Nature -- Effect of human beings on; Environmental protection; Global environmental change